PEMBERDAYAAN MASYARAKAT DI KAWASAN AGROPOLITAN KABUPATEN KEDIRI - Dwinata, Anggara; Faizi, Ahmad; Salamah, Evi Rizqi; Pratiwi, Emy Yunita Rahma; Nugroho, Meriana Wahyu; Af'idah, Noer; Astutik, Leny Suryaning (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Kediri is one of the regencies in East Java Province with a variety of potential natural resources. In Kediri Regency, there are various potentials and natural resources that can support the welfare of the community spread across several sub-districts. The potential and natural resources that exist can be used as an agropolitan area in order to empower the community. Through the implementation method based on regional area design, sector implementation, and impact on the community which are the three main phases in an effort to increase the spirit of skilled and creative work for the community in the agropolitan area of ​​Kediri Regency. The potential and natural resources that can be maximized for export, processing, and creation into productivity in the agropolitan area include: 1) pineapple, papaya, sorgum, and turmeric which can be maximized in the sub-districts of Ngancar, Wates, Plosoklaten, and Kandat, 2) oyster mushrooms, corn, dragon fruit, and sugar cane which can be maximized in the sub-districts of Ngadiluwih, Ringinrejo, and Kras, 3) chili and vegetables which can be maximized in the sub-districts of Pare, Kandangan, Puncu, and Kepung, 4) rice and secondary crops which can be maximized in the sub-districts of Pagu, Plemahan, Papar, and Purwoasri, and 5) podang mango, coffee, orange, and cassava which can be maximized in the sub-districts of Semen, Grogol, Banyakan, Tarokan, and Mojo. Through the distribution map that has been designed by the Kediri Regency Government, it at least provides an illustration to be maximized massively and sustainably in order to increase income and the economy for the people of Kediri Regency.